Validation gas chromatography-fid method for analysis of ethanol content in vinegar - Indah Noviyanti Ruhmana Pulungan; Sugijanto Kartosentono; Amirudin Prawita (Journal of halal product and research (JPHR), 2018)
Production process of vinegar could be synthesized by chemical or microbiological. In Islam, vinegar must not be consumed if contains ethanol ≥ 1%, because it is categorized into khamr. The maximum concentration of vinegar fermentation is 1,0 %. This research was to analyze the alcohol compund that consist in vinegar. The validation method that used in this study are: selectivity, linearity, range, precision, accuracy, LOD and LOQ. The analysis instrument was gas chromatography Agilent 6890 Series GC System, with a Flame Ionization Detector (FID) and a column HP-5 (5% Phenyl 95% Methyl Siloxane), and optimal conditions were obtained by using temperature of inlet and detector of 250°C whilst the temperature of oven programed initially at 40°C, hold for 5 minutes, and raised to 5°C/min to 200°C. were used in this study. For split ratio was achieved at 50:1 and the injection volume was 1.0µl. The methods were proven selective and demonstrated linearity, precision and accuracy with r = 0.9995; 5,63% and 101,25%, respectively. On the other hand, the methods were proven that the sample contains alcohol. Finally, the result of quantitative ethanol contents analysis in vinegar from Saudi Arabia is 2,28.10-2  % v/v; and vinegar brand “x” from market in Surabaya is 1,17.10-2 v/v.